Internal consistency and concurrent validity of self-report components of a new instrument for the assessment of suicidality, the Suicide Ideation and Behavior Assessment Tool (SIBAT). (October 2021) - Chan, Eric C.; Wallace, Keanna; Yang, Esther H.; Roper, Leslie; Aryal, Garima; Lodhi, Rohit J.; Baskys, Andrius; Isenberg, Richard; Carnes, Patrick; Green, Bradley; Aitchison, Katherine J.
Highlights: The Suicide Ideation and Behavior Assessment Tool (SIBAT) is a new rating scale. Convergent validity of the SIBAT was assessed by comparing responses with those from the suicidality component of the MINI. The internal consistency of the studied self-report components of the SIBAT was high. There was good concurrent validity between the SIBAT and MINI items compared. The median completion time of the studied self-report components of the SIBAT was 14.3 min. Abstract: This study aimed to assess the internal consistency of self-report components of the Suicide Ideation and Behavior Assessment Tool (SIBAT) and validate it with relevant elements of the Mini International Neuropsychiatric Interview (MINI). The SIBAT is a newly developed instrument for the evaluation of suicidality. In this study, we invited university students and trainees participating in a study of addictions to complete the self-report component of the SIBAT as an add-on study. We evaluated the internal consistency of the self-report component of the SIBAT and validated it against the suicidality component of the MINI. Data were analysed using both complete case analysis and multiple imputation. SIBAT data were collected for 394 participants, 314 of whom had also completed the MINI. The internal consistency of modules 2, 3, and 5 of the SIBAT was high. Each item from module 5 had a statistically significant association with the corresponding item from the MINI. The sum of scores from modules 2 and 3 had a moderate correlation with the assessment of suicide risk determined by the MINI, and a strong correlation with the total score of SIBAT module 5. The completion median time of modules 2, 3 and 5 was 14.3 min.